A systematic review of geospatial representation of United States community water systems. Issue 1 (9th January 2022) - McDonald, Yolanda J.; Anderson, Kayla M.; Caballero, Mariah D.; Ding, Ke Jack; Fisher, Douglas H.; Morkel, Caroline P.; Hill, Elaine L.
Abstract: This study presents a state‐level systematic review of geospatial representation of Community Water Systems (CWSs) in the United States. We conducted online searches and contacted government, water industry, and academic representatives to obtain these data. CWS geospatial data were characterized by vector type, methodological approaches, data sources, availability to the public, entities involved in creation and maintenance of data, and CWS map requirements by primacy agency. We found that 24 states and the District of Columbia had geospatial representation of CWS estimated service area boundary (ESAB) (i.e., polygons), which were harmonized to construct a geospatial database representative of available CWS ESABs. Our findings aim to prompt discussion among myriad stakeholders on the need to create, standardize, and maintain CWS ESABs to ensure water justice for all communities.